2001
DOI: 10.1046/j.1524-4725.2001.00208.x
|View full text |Cite
|
Sign up to set email alerts
|

Microcystic Adnexal Carcinoma: Report of 13 Cases and Review of the Literature

Abstract: We update the medical literature with 13 MAC cases treated by MMS. To our knowledge there have been 148 cases of MAC reported in the world literature. Including our series, there have been 73 cases of MAC treated with MMS. There were only four treatment failures. Regional and/or distant metastasis from MAC is rare, with only one reported death. Following MMS, the 2-year success rate was 89.7% (35 of 39). The accumulated data continue to confirm that when MAC is discovered early and is readily accessible to exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
125
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(132 citation statements)
references
References 56 publications
5
125
0
1
Order By: Relevance
“…These tumors are able to develop gradually for a number of months or years in a locally aggressive mode. MACs have a 50% postoperative local recurrence rate, with very rare instances of metastasis (1,2,11). The macroscopic characteristics of the MAC case reported in the present study were similar to those reported in previous literature (2,3,7,9,10).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These tumors are able to develop gradually for a number of months or years in a locally aggressive mode. MACs have a 50% postoperative local recurrence rate, with very rare instances of metastasis (1,2,11). The macroscopic characteristics of the MAC case reported in the present study were similar to those reported in previous literature (2,3,7,9,10).…”
Section: Discussionsupporting
confidence: 88%
“…Chiller et al (18) observed that the size of the affected surface area after full excision with MMS was four times larger compared with the clinically apparent size. Therefore, this method ensures complete excision of the cancerous tissue, and subsequently the recurrence rates following MMS are low (0-12%) (11). In the present study, the patient was treated with MMS following reconstruction, and no tumor recurrence was detected during the three-year follow-up period.…”
Section: Discussionmentioning
confidence: 62%
“…[85][86][87][88] Clinically, MAC overlaps with BCC as a light-tan, smooth, firm lesion primarily affecting the central face, head, and neck of adult patients of all ages. [85][86][87]89 Histologically, MAC is an ill-defined, infiltrative lesion that extends deep in the dermis (Figure 6). 85,86,89 Deceptively bland squamoid and basaloid cells form tubular and ductal structures that are haphazardly distributed in a desmoplastic stroma (Figure 6, B).…”
Section: Microcystic Adnexal Carcinomamentioning
confidence: 99%
“…85,86,89 Horn cysts, primarily in the superficial portion of the lesion, and eosinophilic secretions within the ductal lumens are frequently identified. 86,87 Mitotic activity is rare to absent. Perineural invasion is common and often a helpful diagnostic finding.…”
Section: Microcystic Adnexal Carcinomamentioning
confidence: 99%
“…Local recurrence rates are approximately 50%. [210][211][212][213][214] Occasionally, the lesion will appear in unusual locations and settings, such a recent case arising in the external auditory canal 15 years after radiotherapy of a nasopharyngeal carcinoma that had occurred in a 12-year boy. 215 Another patient showed the synchronous development of a microcystic adnexal carcinoma with a gastric carcinoma.…”
Section: Introductionmentioning
confidence: 99%